Variability in grading of ductal carcinoma in situ among an international group of pathologists - Maartje vanSeijen; Katarzyna Jóźwiak; Sarah E Pinder; Allison Hall; Savitri Krishnamurthy; Jeremy SJ Thomas; Laura C Collins; Jonathan Bijron; Joost Bart; Danielle Cohen; Wen Ng; Ihssane Bouybayoune; et al. (Wiley, 2021)
Abstract The prognostic value of cytonuclear grade in ductal carcinoma in situ (DCIS) is debated, partly due to high interobserver variability and the use of multiple guidelines. The aim of this study was to evaluate interobserver agreement in grading DCIS between Dutch, British, and American pathologists. Haematoxylin and eosin‐stained slides of 425 women with primary DCIS were independently reviewed by nine breast pathologists based in the Netherlands, the UK, and the USA. Chance‐corrected kappa (κma) for association between pathologists was calculated based on a generalised linear mixed model using the ordinal package in R. Overall κma for grade of DCIS (low, intermediate, or high) was estimated to be 0.50 (95% confidence interval [CI] 0.44-0.56), indicating a moderate association between pathologists. When the model was adjusted for national guidelines, the association for grade did not change (κma = 0.53; 95% CI 0.48-0.57); subgroup analysis for pathologists using the UK pathology guidelines only had significantly higher association (κma = 0.58; 95% CI 0.56-0.61). To assess if concordance of grading relates to the expression of the oestrogen receptor (ER) and HER2, archived immunohistochemistry was analysed on a subgroup (n = 106). This showed that non‐high grade according to the majority opinion was associated with ER positivity and HER2 negativity (100 and 89% of non‐high grade cases, respectively). In conclusion, DCIS grade showed only moderate association using whole slide images scored by nine breast pathologists. As therapeutic decisions and inclusion in ongoing clinical trials are guided by DCIS grade, there is a pressing need to reduce interobserver variability in grading. ER and HER2 might be supportive to prevent the accidental and unwanted inclusion of high‐grade DCIS in such trials.